Finite element analysis of heat flow through longitudinal finned tubes in the LNG ambient air vaporizer for a total frost case - Lisowski Filip (EDP Sciences, 2021)
Liquefied natural gas (LNG) is transported and stored in liquid state at temperature of -163C. In order to use natural gas directly in its gaseous form, LNG must be vaporized, which requires the input of heat. Ambient air vaporizers (AAVs) are commonly used for that purpose in LNG regasification stations. These heat exchangers consist of longitudinally finned tubes with a large heat transfer surface area, provide high efficiency and are virtually cost-free since the heat is taken from the ambient air. This paper presents the results finite element thermal analysis of heat transfer through the finned tubes of ambient air vaporizers under the conditions of total frosting.